The use of the Godin-Shephard Leisure-Time Physical Activity Questionnaire in oncology research: a systematic review. Issue 1 (December 2015) - Amireault, Steve; Godin, Gaston; Lacombe, Jason; Sabiston, Catherine
Abstract Background The Godin-Shephard Leisure-Time Physical Activity Questionnaire (GSLTPAQ) is one of the most often used questionnaires in oncology research, yet modifications to the scale are done with little evidence of psychometric testing. This study aimed to (i) document the frequency of use of the questionnaire for ranking (i.e., level of activity) and classification (i.e., active versusinsufficiently active ) purposes, (ii) summarize how the GSLTPAQ is used in terms of item content and scoring, and (iii) evaluate the extent to which validity evidence supports the use of the scale among cancer survivors. Methods A systematic review was conducted with evidence drawn from English-written articles published between January 1st 1985 (year the GSLTPAQ was published) and December 31, 2014. A search of six databases, a scan of reference list of included articles, and a cited reference search identified articles that reported using the GSLTPAQ among cancer survivors. Results A total of 212 articles were retrieved. The GSLTPAQ was used for classifying cancer survivors intoactive andinsufficiently active categories in 51 % of the articles. Moreover, a modified version of the questionnaire was used in 81 % of the research studies. Three studies reported validity evidence based on the relationship between the scores on the GSLTPAQ (i.e., leisure score index, LSI) and accelerometer or pedometer-derived activity data. Validity evidence supporting the use of the GSLTPAQ for assessing changes in LSI was computed from six randomized trials. Conclusions The use of the GSLTPAQ for classification purpose in oncology research is common. Standardization in the use and interpretation of the GSLTPAQ in oncology research is warranted. Although limited, there is support for using the original form of the GSLTPAQ and interpreting the LSI for ranking cancer survivors from the lowest to highest levels of leisure-time physical activity.